Features of psycho-physiological indicators in various types of wrestling - Yura Tropin; Natalya Boychenko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: establish the characteristics of the manifestation of psycho-physiological reactions in various types of wrestling. Material & Methods: analysis of scientific and methodological information, generalization of advanced practical experience, psycho-physiological research methods, methods of mathematical statistics. The study involved 30 qualified athletes involved in various types of wrestling, aged 19 to 22 years. Participants were divided into 2 groups of 15 people: 1 - Greco-Roman and freestyle wrestling; 2 - judo and sambo. Athletes were qualified as master of sports and candidate of master of sports. Results: simple, complex motor reactions and specific perceptions of wrestlers were evaluated. In the course of the study, it was determined that the best indicators of simple reactions are observed in representatives of judo and sambo (from 1% to 4%), while in Greco-Roman and freestyle wrestlers, results in complex reactions (from 1% to 13%) and specific perceptions (from 5% to 14%). Conclusions: it was established that different types of wrestling form the ability to quickly analyze, evaluate and predict situations and make the right decisions in a timely manner during the fight, which explains the unreliable differences (p>0,05) in the psycho-physiological indicators of the athletes studied.